Bioaccumulation of PAHs in marine zooplankton: an experimental study in the copepod Pseudodiaptomus marinus - Arias, Andres Hugo; Souissi, Anissa; Roussin, Marion; Oudanne, Baghdad; Souissi, Sami (Environmental Earth Sciences)
Laboratory exposure experiments were performed on the marine coastal zooplankton species Pseudodiaptomus marinus—a keystone species of vast Atlantic and Pacific marine ecosystems, tracing the accumulation of three polycyclic aromatic hydrocarbons (PAHs): phenanthrene, anthracene and pyrene. The experiment was designed to study the bioconcentration of PAHs in phytoplankton (Rhodomonas baltica) and accumulation in copepods (P. marinus), through two different pathways: food and water uptake. For this purpose, water and organism subsamples were collected, ASE (accelerated solvent extraction) extracted, and analyzed for PAHs by GC/MS technique. As a result, experimental bioconcentration (BCF) and bioaccumulation (BAF) factors which showed a significant correlation with the octanol–waterpartition coefficient (Kow) were presented for P. marinus. The active feeding route of exposure showed no significant differences versus passive uptake, highlighting the importance of dietary exposure as a major pathway for POPs accumulation in zooplankton; in particular for those which cannot be metabolized. Fil: Arias, Andres Hugo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Instituto Argentino de Oceanografía. Universidad Nacional del Sur. Instituto Argentino de Oceanografía; Argentina. Universidad Nacional del Sur; Argentina Fil: Souissi, Anissa. Centre National de la Recherche Scientifique; Francia. Universite Lille 3; Francia Fil: Roussin, Marion. Centre National de la Recherche Scientifique; Francia. Universite Lille 3; Francia Fil: Oudanne, Baghdad. Centre National de la Recherche Scientifique; Francia. Université de Lille 1; Francia Fil: Souissi, Sami. Centre National de la Recherche Scientifique; Francia. Universite Lille 3; Francia